Adapting to climate change: lessons from Chile’s coastal communities - Jessica Parra; Magdalena Jensen (International Journal of Climate Change Strategies and Management)
Purpose – This study aims to examine the intricate relationship between Chile’s coastal communities and the increasing effects of climate change, with a focus on Caleta Lenga as a case study. Chile’s extensive coastline is closely linked to the country’s economic well-being and the livelihoods of millions of people. The mounting threats posed by climate change require immediate action. To strengthen resilience and reduce risk, adaptive measures are imperative. However, effective adaptation is hindered by numerous barriers, including adaptive capacity and governance challenges. Design/methodology/approach – This study uses a case study approach, which centres on Caleta Lenga’s unique socio-environmental and demographic context. This study used semi-structured interviews and historical reconstruction to reveal a socio-economic and environmental narrative that was influenced by significant events and transitions. Findings – The residents’ perception of climate change impacts was viewed through the lens of industrial activities and changing weather patterns. This study emphasizes the community’s resilience in the face of changing socio-environmental dynamics. It highlights the importance of informed decision-making, community cooperation and the preservation of ancestral knowledge in promoting adaptive strategies based on community solidarity and collective decision-making. The findings underscore the need for effective adaptation measures that address both adaptive capacity and governance challenges to bolster climate resilience in vulnerable coastal communities. Originality/value – The findings underscore the need for effective adaptation measures that address both adaptive capacity and governance challenges to bolster climate resilience in vulnerable coastal communities.